Introduction des langues nationales dans l'enseignement: attitude des maîtres de Bamako (Nordic Journal of African Studies, 2000)
It is commonly thought that in many African countries, people’s attitudes to the national languages as a medium of instruction are negative, that they prefer the European language because of its prestige and the social opportunities it offers. This article investigates the attitudes of teachers in primary school, key persons in the matter since they are the ones who teach in the national languages. An enquête was carried out in Bamako in 1990 and the results are re-examined ten years later in the light of the recent generalisation of such instruction. The conclusion is that teachers are more positive than one would think, and that the main reason for the positive attitude is sufficient information. Other variables like age, experience, level of instruction and geographical and social origin, play a lesser role. The educational authorities should therefore initiate campaigns to inform the teachers and the rest of the population of the usefulness of the national languages as means of instruction.